The City According to Mike Leigh - Śliwińska, Anna (Wydawnictwo Naukowe UAM w Poznaniu; Wydawnictwo PWSFTViT w Łodzi, 2013)
The key to the interpretation of the image of London presented in Mike Leigh’s films can be found in his own words: “I actually do think London is a hidden city the way New York isn’t.” and “You can get the hang of New York, but London is a collection of villages. It takes a long time to get under its skin.” London in Mike Leigh’s films perfectly matches the director’s creative thought, exposing social differences and the lack of communication in the family. However, the director releases his characters from the dark corners and hideous streets, and lets more light and nature into their lives. Thanks to this, as he has said, the city becomes a collection of small villages, which for him is the greatest value of the place where he lives and makes his films.

Kluczem do interpretacji wizerunków Londynu w twórczości Mike’a Leigh pozostają słowa samego reżysera: “Myślę, że Londyn jest ukrytym miastem w sposób, w jaki Nowy Jork nie jest.” oraz “Możesz uchwycić ideę Nowego Jorku, ale Londyn jest zbiorem wiosek. Zajmuje dużo czasu zanim wnikniesz pod jego skórę.” Londyn w filmach Leigh idealnie wpisuje się w myśl twórczą reżysera. Obnaża różnice społeczne i brak komunikacji w rodzinie. Coraz częściej jednak udaje się reżyserowi wyzwolić swoich bohaterów z ciemnych zakamarków i szpetnych ulic, w zamian za to wpuścić do ich życia więcej światła, pozwolić na kontakt z naturą. Dzięki temu, zgodnie ze słowami reżysera, miasto staje się zbiorem małych wsi, to zaś sam Leigh uważa za największą wartość miejsca, w którym przyszło mu żyć i robić filmy.
Miasto według Mike’a Leigh
Keywords: Mike Leigh; city; London; relationships; family; miasto; związki; rodzina